Análisis de la planta turística oferta alimentación, cantón Pujilí - Andrade Oña, Michael Danny (2021)
The research was focused on the improvement of food service inventories, for which an analysis of the cadastre and a field investigation were developed, this in order to know which are those establishments that are still in operation, in addition to carrying out a catalog for more information for tourists, in this way it contributes to the partial growth of the economy of the Pujilí canton and of the owners. For the fulfillment of the investigation, three objectives were worked, the first objective being the realization of a situational diagnosis by means of the collection of primary and secondary information, with which the current state of the study area was demonstrated, both environmental, socio-cultural, economic and tourist activity, obtaining as a result that economic activity is centered on livestock, agriculture and very few people are engaged in tourist activity despite having great natural and cultural resources; For the fulfillment of the second objective, it was based on the tourism registry of the Ministry of Tourism of the year 2020 where 15 establishments are registered, at the time of the inventory some of the establishments had closed due to the pandemic that hit worldwide , obtaining a total of 29 restaurants, 6 bars, 6 cafeterias, 0 discotheques, 0 mobile establishments, 0 food courts, 0 catering service; For the third objective, a tourist catalog was designed by processing the information obtained from the food supply tourist plant of the Pujilí Canton, this in order to have the correct and precise information on the inventoried establishments